2013
DOI: 10.1038/mt.2013.120
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of VEGF siRNA and Gemcitabine Monophosphate in a Single Nanoparticle Formulation for Effective Treatment of NSCLC

Abstract: There is an urgent need for new therapeutics for the treatment of aggressive and metastatic refractory human non-small-cell lung cancer (NSCLC). Antiangiogenesis therapy and chemotherapy are the two major treatment options. Unfortunately, both types of therapies when used individually have their disadvantages. Integrating antiangiogenesis therapy with chemotherapy is expected to target the tumor's vascular endothelial cells and the tumor cells simultaneously. In this study, we coformulated Vascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 27 publications
1
101
0
Order By: Relevance
“…The co-delivery formulation achieved complete inhibition of tumor growth in 8 days [112] Gemcitabine and C-MYC…”
Section: Anisamidementioning
confidence: 98%
See 1 more Smart Citation
“…The co-delivery formulation achieved complete inhibition of tumor growth in 8 days [112] Gemcitabine and C-MYC…”
Section: Anisamidementioning
confidence: 98%
“…To facilitate co-delivery, CaP-polymer or CaP-liposome hybrid delivery systems have been developed. Zhang et al loaded both VEGF siRNA and gemcitabine monophosphate in the CaP core of the targeted CaP-liposome (i.e., CaP core liposome shell nanoparticle, LCP) hybrid nanoparticle for the combination of chemotherapy and antiangiogenesis therapy (Figure 7) [112]. The co-delivery formulation achieved complete inhibition of tumor growth in 8 days.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Thus, Gemcitabine monophosphate (GMP) and vascular endothelial growth factor (VEGF) siRNA were entrapped into NPs composed of a calcium phosphate core coated with a single lipid bilayer (LCP) [139]. The antitumor effect of such LCP formulation was evaluated against H460 human non small-cell lung cancer (NSCLC) cells.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The antitumor effect of such LCP formulation was evaluated against H460 human non small-cell lung cancer (NSCLC) cells. It was found that the antiangiogenesis treatment with VEGF siRNA combined with the chemotherapy by GMP resulted in an additive antitumor effect better than with VEGF siRNA or GMP alone [139]. Finally, among the gene-silencing technique, miRNA recently gained a great deal of interest, also in lung diseases [116].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Small (30 nm) DNA calcium phosphate nanoparticles are not only endocytosed and trafficked through cells [103,104], but have been adapted for in vivo after encapsulation by cationic lipids. Calcium phosphate nanoparticles were modified with PEG and targeting ligand, and shown to produce efficient gene transfer of DNA, siRNA and mRNA in vivo [56,105,106]. Galactose targeted calcium phosphate nanoparticles resulted in the most efficient gene delivery system for liver hepatocytes reported to date [56] achieving a level of 1% transfection efficiency relative to dose matched hydrodynamic delivery.…”
Section: Packaging Dna Into Blood Compatible Nanoparticlesmentioning
confidence: 99%